Gerakan Lingkungan Menolak Alih Fungsi Lahan Kampus Akademi Penyuluh Pertanian (APP) Kota Malang, 1993-2007 - Izzah, Rikmaya Nur; Ridhoi, Ronal (Sasdaya: Gadjah Mada Journal of Humanities, 2025)
The land conversion of the Malang Agricultural Academy Campus into Ijen Nirwana housing is a reflection of land use change that occurs in urban areas. The event caused various environmental and social problems such as the loss of flora and fauna, the phenomenon of prolonged flooding, and the unrest that occurred in the community of Malang City. This paper attempts to narrate the history of land use change and various environmental movements that have occurred in Malang City in order to increase public awareness of the importance of Green Open Space (RTH) as a counterweight to urbanization. The author uses the historical method which includes topic selection, heuristics, verification, interpretation, and historiography through various interviews and document analysis using a political environmental history perspective. The author found that changes in spatial policies, weak laws, and economic interests were the main factors in the decision to change the land function of APP Malang Campus. This phenomenon caused various responses among the people of Malang City at that time, various rejections were made but could not fully defend the Malang City Agricultural Extension Academy Campus land. This kind of intersection between capitalism and environmental interests often occurs even after the New Order era.